New Economic Geography and the Conception of Social Factors of Criminality: Areas of Common Interest and Prospects for Synthesis - Bakharev, Dmitry V. (International Journal of Criminology and Sociology, 2014)
The article discusses the application of «new economic geography» in investigating the reasons for territorial distinctions and other factors of criminality.